2016
DOI: 10.1002/ima.22198
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory identification and white matter integrity in amnestic mild cognitive impairment: A preliminary study

Abstract: Increasing evidence suggests that olfactory impairment is associated with an increased risk of conversion from mild cognitive impairment (MCI) to Alzheimer's disease. This study was to explore how olfactory identification relates to white matter (WM) integrity, using diffusion tensor imaging (DTI) in individuals with amnestic MCI. DTI was performed from nineteen individuals with amnestic MCI (mean age: 69.95 6 8.20 years). Olfactory identification was assessed using the Cross-Cultural Smell Identification Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…One study found that total volume of white matter hyperintensities was not associated with UPSIT scores among those with MCI and cognitively normal participants, 19 and another found that gray matter changes were more prominent compared to white matter changes among AD participants 36 . In contrast, three studies found that olfactory identification scores were associated with white matter alterations among those with MCI and AD 21,34,35 …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…One study found that total volume of white matter hyperintensities was not associated with UPSIT scores among those with MCI and cognitively normal participants, 19 and another found that gray matter changes were more prominent compared to white matter changes among AD participants 36 . In contrast, three studies found that olfactory identification scores were associated with white matter alterations among those with MCI and AD 21,34,35 …”
Section: Resultsmentioning
confidence: 98%
“…Among case series (n = 4) with no control groups, 21,23,30,35 two studies found that hippocampal atrophy was associated with olfactory dysfunction 21,23 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations